2021
DOI: 10.3390/cancers13205127
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Values of Myeloid-Derived Suppressor Cells in Hepatocellular Carcinoma: Facts and Hopes

Abstract: One of the major challenges in hepatocellular carcinoma (HCC) treatment is drug resistance and low responsiveness to systemic therapies, partly due to insufficient T cell infiltration. Myeloid-derived suppressor cells (MDSCs) are immature marrow-derived cell populations with heterogeneity and immunosuppression characteristics and are essential components of the suppressive tumor immune microenvironment (TIME). Increasing evidence has demonstrated that MDSCs are indispensable contributing factors to HCC develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 124 publications
(173 reference statements)
0
9
0
Order By: Relevance
“…In conclusion, MDSCs have two main functions: on the one hand, it promotes tumor progression by inhibiting the anti-tumor function of T cells and NK cells; on the other hand, MDSCs also promote new angiogenesis and tumor cell invasion 53 . Previous studies have shown that MDSCs from HCC patients can inhibit the cytotoxicity and cytokine secretion of NK cells when cultured with NK cells in vitro 54 . MDSCs can express high levels of PD-L1, and can also recruit Tregs by expressing CD40.…”
Section: The Immune Network In Tme Of Hccmentioning
confidence: 98%
“…In conclusion, MDSCs have two main functions: on the one hand, it promotes tumor progression by inhibiting the anti-tumor function of T cells and NK cells; on the other hand, MDSCs also promote new angiogenesis and tumor cell invasion 53 . Previous studies have shown that MDSCs from HCC patients can inhibit the cytotoxicity and cytokine secretion of NK cells when cultured with NK cells in vitro 54 . MDSCs can express high levels of PD-L1, and can also recruit Tregs by expressing CD40.…”
Section: The Immune Network In Tme Of Hccmentioning
confidence: 98%
“…PMN-MDSCs are mainly enriched in TIME and generate large amounts of reactive oxygen species (ROS) to mediate T cell tolerance. However, M-MDSCs accumulate in peripheral blood expressing high levels of iNOS but releasing low ROS to suppress the immune response [ 85 ]. Emerging studies have shown that CAFs could promote the generation of MDSCs through paracrine manner.…”
Section: The Roles Of Cafs In Hcc Progressionmentioning
confidence: 99%
“…MDSCs can be classified into two groups: monocytic and polymorphonuclear. The monocytic MDSCs inhibit T cell responses through the production of anti-inflammatory cytokines and nitric oxide, whereas the polymorphonuclear MDSCs suppress T cells by generating peroxynitrite, which nitrates T cell receptors to reduce their responsiveness to antigen-MHC complexes [ 24 , 25 , 26 ].…”
Section: The Immune Microenvironment Of Hccmentioning
confidence: 99%